2020
DOI: 10.3390/jcm9092754
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Antenatal Diagnostic Criteria of Twin-Anemia-Polycythemia Sequence

Abstract: This study aims to elicit the validation performance of different diagnostic criteria and to evaluate the disease course and perinatal outcomes of pregnancies complicated by twin anemia polycythemia sequence (TAPS). Monochorionic diamniotic (MCDA) twin pregnancies who received serial middle cerebral artery (MCA) peak systolic velocity (PSV) measurements without non-TAPS-related demise or major anomalies were included. Course of disease, antenatal intervention, additional ultrasound features, and perinatal outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…22 In our study there was no difference in the incidence of coexistent sFGR between groups with incidence ranging between 35% and 45%, similar to the incidence seen in other studies. 17,23 Few studies suggested an association between TAPS and sFGR, 24,25 however this could be secondary to the fact that sFGR fetuses have been found to have higher MCA PSV values 26 which might result in higher delta PSV or may be due to unequal placental sharing. 27 Treatment options for TAPS include expectant management, intrauterine blood transfusion (IUT) in the donor, fetoscopic laser…”
Section: Discussionmentioning
confidence: 99%
“…22 In our study there was no difference in the incidence of coexistent sFGR between groups with incidence ranging between 35% and 45%, similar to the incidence seen in other studies. 17,23 Few studies suggested an association between TAPS and sFGR, 24,25 however this could be secondary to the fact that sFGR fetuses have been found to have higher MCA PSV values 26 which might result in higher delta PSV or may be due to unequal placental sharing. 27 Treatment options for TAPS include expectant management, intrauterine blood transfusion (IUT) in the donor, fetoscopic laser…”
Section: Discussionmentioning
confidence: 99%
“…(6,8,9,16,20,21,31,33,34,43) The existence of a wide spectrum of incidence may result from differences between laser surgical techniques, color dye placental injection techniques, differences in classification systems, or the existence of selection bias. (6,20,29,44) The more restrictive the diagnostic criteria that are applied, the lower is the incidence of TAPS. (20) By applying Solomon's technique, instead of a selective approach, in the treatment of TTTS, it is possible to reduce the incidence of iatrogenic TAPS from 16% to approximately 3%.…”
Section: Epidemiologymentioning
confidence: 99%
“…(22) Subsequently, a more conservative approach regarding the cutoff for the recipient (MCA-PSV < 1.0 MoM)) was proposed. (9,16,20,22,23,31,44) Fishel-Bartal et al demonstrated that twin differences in MCA-PSV values were positively correlated with postbirth hematocrit discordances and that polycythemia could not be excluded even if the MCA-PSV was not low. (25,29,85) On this premise, several subsequent studies have stated that the difference between a peak maximum systolic velocities of both twins (∆MCA-PSV) superior to 0.5 multiples of the median (MoM) could have greater diagnostic accuracy for predicting TAPS than the current MCA-PSV cutoff criteria and that ∆MCA-PSV is a good predictor of the neonatal intertwin hemoglobin concentration difference and potentially of TAPS.…”
Section: Diagnostic Criteria 51 Prenatal Diagnosismentioning
confidence: 99%
“…The reluctance to adopt routine antenatal monitoring for TAPS, as evidenced in the NICE and American College of Obstetricians and Gynecologists guidelines 70,72 , could be explained by the scarce data on the natural history of TAPS, validation of the antenatal diagnostic criteria, perinatal outcome and the optimal management strategy. Over the last few years, researchers have been aiming to address some of these uncertainties, including a Delphi consensus on the antenatal diagnostic criteria for TAPS 73 , a validation study of these criteria 74 and a multicenter international registry reporting on the perinatal outcome of twin pregnancies complicated by TAPS according to onset, severity and management option [23][24][25] .…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%